PENGARUH MODEL PROBLEM-BASED LEARNING BERMUATAN TRI KAYA PARISUDHA TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SEKOLAH DASAR - I Gede Arya Wiradnyana; Agus Budhi Arya Pramana, Komang; Santika, Made; Witana, I Nyoman (Adi Widya: Jurnal Pendidikan Dasar, 2026)
Critical thinking skills in mathematics constitute a fundamental competency that requires development at the elementary school level. However, existing learning practices often remain suboptimal due to insufficient reinforcement of character values. This study aims to investigate the effectiveness of integrating Tri Kaya Parisudha (TKP) values into the Problem-Based Learning (PBL) model on students' mathematical critical thinking skills. Utilizing a quantitative approach with a Quasi-Experimental Pre-test Post-test Control Group Design, the research involved fourth-grade elementary students in Cluster I, Buleleng District. Cluster random sampling was employed to select State Elementary School 1 Anturan (28 students) as the experimental class and State Elementary School 2 Anturan (36 students) as the control class. A validated and reliable essay test was utilized as the instrument to measure critical thinking skills. The Independent Sample t-test results yielded a significance value of 0.000 (<0.05) with a t-value of 8.247, indicating a significant effect. The experimental class achieved a mean post-test score of 78.45, substantially surpassing the control class's score of 62.18. The improvement in critical thinking skills within the experimental class was categorized as moderate (N-Gain 0.59), whereas the control class showed low improvement (N-Gain 0.28). In conclusion, the PBL model enriched with TKP values is proven to be more effective in enhancing mathematical critical thinking skills compared to conventional learning.